2017
DOI: 10.5010/jpb.2017.44.3.287
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Small Heat Shock Protein, PtsHSP19.3 from Marine Red Algae, Pyropia tenera (Bangiales, Rhodophyta) Enhances Abiotic Stress Tolerance in Chlamydomonas

Abstract: This is an Open-Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/4.0) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.Abstract Water temperature is one of the major factors that impacts the growth and life cycle of Pyropia tenera, one of the most valuable and cultivated marine red algae belonging to Bangiales (Rhodophytes). We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
(46 reference statements)
1
7
0
Order By: Relevance
“…3). These results are similar to those of an earlier transgenic study (Jin et al 2017). The expression of the Pyropia tenera HSP19.3 gene inserted into the C. reinhardtii genome is reportedly upregulated soon after initiating a HT treatment and confers Fig.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…3). These results are similar to those of an earlier transgenic study (Jin et al 2017). The expression of the Pyropia tenera HSP19.3 gene inserted into the C. reinhardtii genome is reportedly upregulated soon after initiating a HT treatment and confers Fig.…”
Section: Discussionsupporting
confidence: 90%
“…The expression of the Pyropia tenera HSP19.3 gene inserted into the C. reinhardtii genome is reportedly upregulated soon after initiating a HT treatment and confers Fig. 5 Heat map of the differentially expressed genes involved in the proteasome, ubiquitin-mediated proteolysis, protein processing in the endoplasmic reticulum (ER), and citrate cycle (TCA cycle) between WT-CK (wild-type unstressed control) and HSP-CK (transgenic C. reinhardtii unstressed control) the tolerance to heat (Jin et al 2017). Our data suggest that PhHsp22 from P. haitanensis might play a significant role in resisting HT stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the PysHSPs contained a BI/V-x-I/ V^motif, highly conserved across many sHSPs and affects the oligomerization (Pasta et al 2004). These two conserved motifs have also been found in sHSPs from the red algae P. tenera (Jin et al 2017) and C. merolae (Kobayashi et al 2014). Phylogenetic analysis revealed that All PysHSPs were classified with the clusters of sHSPs from the red algae that were distinct from those of land plants and green algae (Fig.…”
Section: Characterization Of Pyropia Cdnas Encoding Shspsmentioning
confidence: 63%
“…Transcriptome analysis has revealed the upregulation of HSPs, including sHSPs, under high-temperature conditions in Pyropia species (Park et al 2012;Sun et al 2015), and it has also been shown that the overexpression of sHSPs from Pyropia tenera enhances heat stress tolerance in C. reinhardtii (Jin et al 2017). Furthermore, proteome analysis has shown that HSP22 is upregulated under desiccation stress in Pyropia orbicularis (López-Cristoffanini et al 2015).…”
Section: Introductionmentioning
confidence: 99%